REPURPOSED SIMVASTATIN-LOADED NANOSTRUCTURED LIPID CARRIERS: OPTIMIZATION, CHARACTERIZATION AND EVALUATION AGAINST LUNG CANCER - ARA, NARGIS; HAFEEZ, ABDUL; KUSHWAHA, SHOM PRAKASH; KAPOOR, ARCHITA (International Journal of Applied Pharmaceutics, 2025)
Objective: Repurposed Simvastatin (SMV) is being investigated for the treatment of lung malignancies. However, its inadequate solubility in water and formulation constraints are the potential challenges for its use against lung cancer. This study aimed at synthesis of SMV-loaded Nanostructured Lipid Carriers (SMV-NLC) for lung cancer management. Methods: Emulsification and probe sonication approach was chosen for the formulation of NLCs. A three-factor, three-level Box-Behnken design was utilized for the development of SMV-NLC formulation. The independent variables selected were total lipid concentration (%w/w), solid lipid: liquid lipid ratio, and surfactant concentration (%w/w). Screening of components was performed based on SMV solubility and SMV-excipient compatibility studies. Results: Optimized SMV-NLC showed a particle size of 209.8±1.8 nm, low polydispersity index (0.319±0.14), negative zeta potential (-20.35 mV) and good entrapment efficiency (73.51±4.22%). Transmission electron microscopy examination revealed spherical shape of NLC with validation of nanometric size. Fourier Transform Infrared analysis revealed the entrapment of the SMV within the lipid matrix of NLC. SMV release of 86.97±1.7% was obtained from NLC after 24 h with sustained release characteristics. In vitro cytotoxic activity against A549 cell lines (lung cancer) showed IC50of 11.34±0.12 and 30.26±0.14 µg/ml for SMV-NLC and SMV-suspension, respectively. Conclusion: The developed SMV-NLC may be utilized as an effective platform for the management of lung cancer.